Literatur Review: Penyebab dan Dampak Period Poverty di Indonesia - Annisa Nur Faiqah; Nunik Puspitasari (Media Gizi Kesmas, 2023)
Background: Menstruation is a normal biological process that happen in the female body. However, not all women have access to menstrual hygiene products. According to previous research, it shows that there is inequality menstrual hygiene management in low- and middle-income countries, including Indonesia. Objectives: This study aims to review the period of poverty or in Indonesia, starting from the causes, impacts, and efforts to overcome it. Methods: The method used in this research was literature review in descriptive form. The data used in the form of secondary data from articles/journals and books collected through the trusted websites such as Science Direct and Google Scholar, and through the university's official website that published in the last 10 years (2011-2021). Results: Based on the articles that have been collected, the results show that poverty, the lack of comprehensive education regarding health management, lack of access to clean water, soap, sanitation products, and the lack of adequate infrastructure make Indonesia and other developing countries still experience period poverty. The impact can be very detrimental such as limitation for going to school during menstruation, reproductive organs disease, and the risk of experiencing sexual harassment. Providing adequate menstrual hygiene management that is accessible to all women and girls is one of the steps to address this problem. Conclusion: Factors affecting period poverty in Indonesia are poverty, the lack of comprehensive education regarding health management, lack of access to clean water, soap, sanitation products, and the lack of adequate infrastructure. The impacts are in the form of limitation for going to school during menstruation, reproductive organs disease, and the risk of experiencing sexual harassment